2021
DOI: 10.3390/s21196519
|View full text |Cite
|
Sign up to set email alerts
|

An Improvement of the Fire Detection and Classification Method Using YOLOv3 for Surveillance Systems

Abstract: Currently, sensor-based systems for fire detection are widely used worldwide. Further research has shown that camera-based fire detection systems achieve much better results than sensor-based methods. In this study, we present a method for real-time high-speed fire detection using deep learning. A new special convolutional neural network was developed to detect fire regions using the existing YOLOv3 algorithm. Due to the fact that our real-time fire detector cameras were built on a Banana Pi M3 board, we adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…To evaluate and analyze the effectiveness of fire recognition cases, we compared the proposed approach with recently published fire detection methods. To perform this task, we employed widely used estimation metrics for object (static or dynamic) detection, as in our previous publications [16,56]. First, we computed the precision and recall metrics It employs a CSPNet strategy to partition the feature map of the base layer into two parts and subsequently merges them through a cross-stage hierarchy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To evaluate and analyze the effectiveness of fire recognition cases, we compared the proposed approach with recently published fire detection methods. To perform this task, we employed widely used estimation metrics for object (static or dynamic) detection, as in our previous publications [16,56]. First, we computed the precision and recall metrics It employs a CSPNet strategy to partition the feature map of the base layer into two parts and subsequently merges them through a cross-stage hierarchy.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate and analyze the effectiveness of fire recognition cases, we compared the proposed approach with recently published fire detection methods. To perform this task, we employed widely used estimation metrics for object (static or dynamic) detection, as in our previous publications [16,56]. First, we computed the precision and recall metrics Experiments have demonstrated that our improved fire detector can relieve people's anxiety, and it enables the early suppression and rapid response irrespective of the time of day or the shape or size of the fire.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations